2001
DOI: 10.1063/1.1399023
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field and temperature dependence of terahertz radiation from InAs surfaces excited by femtosecond laser pulses

Abstract: The magnetic field (0–5 T) and temperature (10–300 K) dependence of terahertz radiation from InAs surfaces excited by femtosecond laser pulses has been studied in detail. The radiation intensity is strongly enhanced under the magnetic field and at low temperatures, which is explained based on simple classical motion of photoexcited electrons under a built-in surface electric field and Lorentz force undergoing scattering. The radiation spectra are broad even at low temperatures under high magnetic fields, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[65] Singh et al have reported THz generation by mixing two cosh-Gaussian laser beams in a density rippled plasma. We consider the maximum magnetic field strength to be 60 kGauss (kG) or 6 Tesla (T), but there are some experimental references that use magnetic fields from 5 up to 10 T. [74][75][76] In our scheme, the CO 2 laser pulse [37,39] can provide desired frequencies for incident laser beams. [67] Hematizadeh et al have presented a scheme for THz generation based on the nonlinear mixing of two oblique incident laser beams on an over-dense magnetized plasma; they have also reported generation of THz radiation from under-dense plasma by taking advantage of right-hand circularly polarized (RCP) and left-hand circularly polarized (LCP) waves via different laser beam profiles.…”
Section: Introductionmentioning
confidence: 99%
“…[65] Singh et al have reported THz generation by mixing two cosh-Gaussian laser beams in a density rippled plasma. We consider the maximum magnetic field strength to be 60 kGauss (kG) or 6 Tesla (T), but there are some experimental references that use magnetic fields from 5 up to 10 T. [74][75][76] In our scheme, the CO 2 laser pulse [37,39] can provide desired frequencies for incident laser beams. [67] Hematizadeh et al have presented a scheme for THz generation based on the nonlinear mixing of two oblique incident laser beams on an over-dense magnetized plasma; they have also reported generation of THz radiation from under-dense plasma by taking advantage of right-hand circularly polarized (RCP) and left-hand circularly polarized (LCP) waves via different laser beam profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain intense THz emission, earlier works focused on searching a proper compound semiconductor and subsequently adjusted the doping concentration [3][4][5]. Moreover, external magnetic fields, which are of the order of 1 T, were used for enhancing the THz emission [6][7][8][9][10][11] ; however, the THz spectroscopic system with the use of the magnetic field generator lacks the advantage of being convenient.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large number of reports on studies with pulse excitation of semiconductor structures, mostly single or few THz cycles, exists. In most of these investigations, the goal was not the efficient generation of THz radiation, but rather the study of the dynamics of photogenerated carriers in surface depletion layers, 48,49 in semiconductor superlattices, 126 or large electric fields in p-i-n diodes. 120 Therefore, no attempts were made to calibrate the observed signals.…”
Section: -29mentioning
confidence: 99%
“…This induces a surface-parallel component of near-surface carrier transport due to the Lorentz force. [48][49][50] A simpler way to generate strong in-plane components of the carrier acceleration and, hence, strong in-plane components of the THz fields, is with the application of a DC bias to large area coplanar metallic contacts. This creates a strong in-plane electric field.…”
mentioning
confidence: 99%